Czy Pneumocystis jiroveci jest nadal zagrożeniem dla niemowląt? – opis przypadku - Wilińska, Maria; Alster, Piotr; Sułek-Kamas, Katarzyna; Piotrowski, Andrzej; Idziakowska Głuszczak, Ewa; Brzewski, Michał (Pediatria Polska - Polish Journal of Paediatrics, 2017)
Pneumocystis jiroveci is still a dangerous pathogen. The child with extreme immaturity has gone through severe circulatory and respiratory failure after birth, a few episodes of infection including the central nervous system, and has gone through a lot of invasive procedures like intubation, long-term central catheters and parenteral nutrition. Inclusion of trimethoprim and sulfamethoxazole targeted therapy resulted in clinical improvement and gradual resolution of inflammatory changes.